Teacher Creativity in Improving Children's Counting Ability Through the Congklak Game at TK Jabal Nur - Nurfitri Rahmawati; Ihlas; Hermansyah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to describe teacher creativity in improving children’s numeracy skills through the congklak game at TK Jabal Nur. The study employed a qualitative approach with a descriptive design to obtain an in-depth understanding of the learning process, the teacher’s role, and the development of children’s numeracy skills through the congklak game. This design was selected because it enables researchers to describe participants’ experiences and classroom practices in their natural setting rather than to test hypotheses or determine causal relationships. The research involved one teacher and 20 Group B children aged 5–6 years who were selected purposively based on their participation in congklak-based learning activities. Data were collected through observations, semi-structured interviews, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while source and technique triangulation were applied to enhance the credibility of the findings. The findings indicate that teacher creativity was reflected in the design and implementation of engaging congklak-based learning activities that supported children’s numeracy development. Children demonstrated greater participation during learning activities and showed progress in recognizing numbers, counting objects, matching numbers with quantities, and understanding number sequences based on classroom observations and assessment records. The learning activities also provided opportunities for children to develop concentration, logical thinking, cooperation, and social interaction through meaningful play experiences. These findings highlight the importance of integrating traditional games into child-centered learning practices and demonstrate how teacher creativity can enrich numeracy learning experiences in early childhood education.